A rare chromosomal disorder in a newborn: Trisomy 3q - Kahvecioğlu, Dilek; Tatar-Aksoy, Hatice; Yıldız, Eren; Bakır, Abdullatif; Alioğlu, Bülent (The Turkish Journal of Pediatrics, 2019)
Trisomy 3q is a rare chromosomal disorder that leads to multiple congenital abnormalities. We hereby present a patient with chromosomal karyotype 46, XY, dup (3)(q23-29), which can be classified as pure 3q duplication and has thin sclera and iris dysgenesis, anterior and posterior segment dysgenesis besides the previously identified specific facial features. To the best of our knowledge only 12 cases have been reported with pure duplication in the literature. Our case is the 13th one reported and has noval findings concerning eye involvement. The ocular manifestations of the 3q duplication syndrome provide additional evidence of the involvement of genes which are responsible for eye development in this chromosomal region.
Keywords: Cornelia de Lange; iris dysgenesis; trisomy 3q